Рассказы и сказки: [0+] / Л. Н. Толстой - Толстой Лев Николаевич (Лучшая детская книга, 2021)
Экземпляры: ф. 2 (20220126) / Инвентарный номер: 116573 / Цена: 353.10 / Авт.знак: Т 53 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)1